Seeing the Invisible : A Strategic Report on Groundwater Quality - Ravenscroft, Peter; Lytton, Lucy (Washington, DC: World Bank, 2022)
This report describes why, and how, groundwater quality is vital to human health, agriculture, industry and the environment. In turn, this explains why it is so important to World Bank staff and clients, as well as diverse managers and administrators in countries and economies at all stages of development.